A Deeper Look at Hawaiian Coral Reef Fish Assemblages: A Comparison of Survey Approaches and Assessments of Shallow to Mesophotic Communities - Asher, Jacob (Curtin University, 2017)
This PhD provides a comparative analysis between underwater visual censuses, and provides new information on shallow to mesophotic reef fishes/predator communities in the Hawaiian Archipelago. Results show that 1.) 60-minute, baited surveys were most effective in capturing overall populations, 2.) functional group composition shifts between shallow water, upper, and lower-mesophotic zones in the MHI, as do top-level predators in both the MHI and NWHI, and 3.) predator abundances remain inconsistent between diver and video-based methodologies.